An unexpected tail of VEGF and PlGF in pre-eclampsia - Bates, David O (2011)
Pre-eclamptic toxaemia (PET), characterised by pregnancy related hypertension and proteinuria, due to widespread endothelial dysfunction, is a primary cause of maternal morbidity. Altered circulating factors, particularly the VEGF family of proteins and their receptors, are thought to be key contributors to this disease. Plasma from patients with PET induces numerous cellular and physiological changes in endothelial cells indicating the presence of a circulating imbalance of the normal plasma constituents. These have been narrowed down to macromolecules of the VEGF family of proteins and receptors. It has been shown that responses of endothelial cells in intact vessels to plasma from patients with pre-eclampsia is VEGF dependent. It has recently been shown that this may be specific to the VEGF(165)b isoform, and blocked by addition of recombinant human PlGF. Taken together with results that show that sVEGFR1 levels are insufficient to bind VEGF-A in human plasma from patients with pre-eclampsia, and that other circulating macromolecules bind but do not inactivate VEGF-A, suggest that novel hypotheses involving altered bioavailability of VEGF isoforms resulting from either reduced, or bound PlGF, or increased sVEGFR1 increasing biological activity of circulating plasma could be tested. This suggests that knowing how to alter the balance of VEGF family members could prevent endothelial activation, and potentially some symptoms, of pre-eclampsia.